Copolymers based on epoxidized soy bean oil and diglycidyl ether of bisphenol a: Relation between morphology and fracture behavior - Altuna, Facundo Ignacio (2014)
Epoxidized soybean oil (ESO) was proved to be a good alternative to partially replace a synthetic commercial epoxy resin in a formulation to obtain thermosetting polymer, contributing to transform a vegetable oil into a higher added value product. This work focuses on the study of the fracture behavior of copolymers based on anhydride-cured epoxy systems with different contents of ESO as a replacement for the synthetic resin. It was found that fracture toughness was greatly improved when replacing diglycidyl ether of bisphenol A (DGEBA) by ESO, being the critical stress intensity factor (KIC) 1.067 MPam1/2 for cured ESO and 0.557 MPam1/2 for cured DGEBA. The better performance of ESO networks was ascribed to its higher ability to attain plastic deformation. Moreover, for DGEBA-ESO systems, the morphologies generated during the curing process were also considered to account for the observed results.